Student Agency through Negotiated Practice - Meg O’Donnell (Middle Grades Review, 2021)
Using the James Beane’s democratic approach, this article describes how a middle grades team support students to choose topics within broad themes and learning pathways that suit their interests, skills, and needs as individuals. Using a series of instructional structures, the facilitators encourage students to engage in research, thoughtful discussions, courageous conversations, and carefully constructed writing processes, while also emphasizing curiosity, critical thinking, relationship development, and social activism. Within a standards-based learning environment the author walks the reader through a process which allows students to generate questions they want to investigate. Once students have generated their common questions, they review the Common Core State Standards and content standards for social studies or science units. This process of democratic education has students taking the leadership role in planning curriculum and having teachers take on the role of facilitator. Ultimately, this article discusses how this process leads to student engagement, provides opportunities for reflection, and allows for students to achieve academic and personal goals while addressing issues for social change.
Keywords: personalized learning; social justice; middle school; young adolescents